Pengaruh Profitabilitas dan Solvabilitas Terhadap Income Smoothing dengan Good Corporate Governance Sebagai Variabel Moderasi Pada Bank Umum Syariah Periode 2019-2021 - Nisa, Khairun; Atika, Atika; Rahmani, Nur Ahmadi Bi (Journal of Computer Science and Information System(JCoInS), 2024)
Financial statements are one of the things that investors need to pay attention to before they invest their funds. However, financial reports are often manipulated for certain purposes, and what is often manipulated is profit reports. This act of earnings manipulation is called earnings management, and the most frequently used strategy is income smoothing. This is certainly contrary to sharia principles that have been carried out by sharia commercial banks. GCG as a company management system is expected to minimize these actions. This study aims to determine what factors influence income smoothing by analyzing its financial performance, namely profitability and solvency. This study uses descriptive quantitative methods with PLS observer tools. The sample in this research is the 2019-2021 sharia commercial bank financial statements. The results of this study indicate that only DAR (Dept to Asset Ratio) has a significant effect on income smoothing, while the other three variables namely ROA (Ratio Of Assets), ROE (Ratio Of Equity), and DER (Dept to Equity Ratio) have no effect on income smoothing. GCG is unable to moderate profitability (ROA and ROE) on income smoothing, and GCG is unable to moderate solvency (DAR and DER) on income smoothing.